The association between social jetlag and parameters of metabolic syndrome and type 2 diabetes: a systematic review and meta-analysis - Bouman, Emma J.; Beulens, Joline W.J.; Groeneveld, Lenka; de Kruijk, Rozemarijn S.; Schoonmade, Linda J.; Remmelzwaal, Sharon; Elders, Petra J.M.; Rutters, Femke (John Wiley & Sons Inc., 2023)
This study aims to determine the association between social jetlag and parameters of metabolic syndrome and type 2 diabetes (T2D) in a systematic review and meta-analysis. A systematic literature search was conducted in PubMed/Embase/Scopus until May 2022. Included studies described an association between social jetlag and parameters of the metabolic syndrome and/or T2D, were available full text and written in English or Dutch. Data extraction and quality assessment were performed on pre-piloted forms independently by two reviewers. Results were meta-analysed using random-effects analysis. A total of 6,290 titles/abstracts were screened, 176 papers were read full-text, 68 studies were included. Three studies were rated as low quality, 27 were moderate, and 38 were high quality. High quality studies showed that having social jetlag compared to no social jetlag was significantly associated with higher body mass index in 20 studies (0.49 kg/m2, 95% confidence interval [CI] 0.21–0.77; I2 = 100%), higher waist circumference in seven studies (1.11 cm, 95% CI 0.42–1.80; I2 = 25%), higher systolic blood pressure in 10 studies (0.37 mmHg, 95% CI 0.00–0.74; I2 = 94%) and higher glycated haemoglobin in 12 studies (0.42%, 95% CI 0.12– 0.72; I2 = 100%). No statistically significant associations were found for obesity, abdominal obesity, high- and low-density lipoprotein levels, cholesterol, triglycerides, diastolic blood pressure, hypertension, fasting glucose, homeostatic model assessment for insulin resistance, metabolic syndrome or T2D. Sensitivity analyses did not reduce heterogeneity. Despite substantial heterogeneity, social jetlag is associated with certain parameters of the metabolic syndrome and T2D, but not with prevalent metabolic syndrome or T2D. These findings should be interpreted with caution as the level of evidence is low and mostly based on cross-sectional data. Longitudinal studies are needed to further assess the direction of causality.
Keywords: meta-analysis; metabolic syndrome; social jetlag; type 2 diabetes; Cognitive Neuroscience; Behavioral Neuroscience